2018
DOI: 10.1016/j.jadohealth.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the Public School System to Combat Adolescent Obesity: The Limits of Arkansas's Statewide Policy Initiative

Abstract: This study assessed the effectiveness of one of the earliest statewide policy initiatives to address obesity via schools-Arkansas's Act 1220 of 2003-on adolescent obesity. The Act required public schools in Arkansas to conduct body mass index (BMI) screening and reporting, restrict access to vending machines and establish physical education and nutrition standards. Methods: To determine the effect of Act 1220 as a whole, this study analyzed data representative of adolescents in grades 9-12 from the Youth Risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Table 2 summarizes the evidence reported separately by a single sociodemographic factor: gender, grade or age, race/ethnicity or socioeconomic indicators. Grade level or age [33][34][35][36][37][38][39][40][41] was the most frequently reported demographic (n = 9), whereas four studies reported results by gender, 33,36,42,43 two papers reported findings by race/ethnicity, 29,36 and two studies displayed results by socioeconomic factors, 36,44 using eligibility for free or reduced-price lunch (FRPL) as a proxy (Figure 2). Six papers reported results jointly stratified by two or more sociodemographic dimensions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 summarizes the evidence reported separately by a single sociodemographic factor: gender, grade or age, race/ethnicity or socioeconomic indicators. Grade level or age [33][34][35][36][37][38][39][40][41] was the most frequently reported demographic (n = 9), whereas four studies reported results by gender, 33,36,42,43 two papers reported findings by race/ethnicity, 29,36 and two studies displayed results by socioeconomic factors, 36,44 using eligibility for free or reduced-price lunch (FRPL) as a proxy (Figure 2). Six papers reported results jointly stratified by two or more sociodemographic dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…36,44 One study used both a cross-sectional, and beforeafter design with a control group, 43 while 10 papers used a before/ after design, 27,34,39,42,45 paired with interrupted time series 30,46,47 or with a control group. 37,43 The latter studies help enhance inferences about policy associations with overweight/obesity, though the length of before-after time periods also varied among studies. Eight of the before and after studies used measured height and weight, whereas six studies used obesity indicators measured at multiple time points before and after the policies were enacted.…”
Section: Quality Of Evidencementioning
confidence: 99%
“…The widespread availability of vending machines has been viewed as a problematic environmental factor contributing to the high consumption of food and drinks of minimum nutritional value (Wiecha et al ., 2006; Thompson et al ., 2010; Callaghan et al ., 2015; O'Hara and Haynes‐Maslow, 2015; Cisse‐Egbuonye et al ., 2016; Raposo et al ., 2018). Consequently, many studies examine the efficacy of public policies and nutritional standards for combating diet‐related diseases from the perspective of schools (Kakarala et al ., 2010; Phillips et al ., 2010; Samuels et al ., 2010; Kubik et al ., 2013; Gee, 2018; Kehm et al ., 2018; Acciai et al ., 2019; Kovacs et al ., 2020), hospitals (Van Hulst et al ., 2013; Champ et al ., 2019; Pechey et al ., 2019; Carrillo‐Álvarez et al ., 2020), sport and recreational centers (Olstad et al ., 2015, 2020; Lane et al ., 2019), and worksite locations (Blanck et al ., 2009; French et al ., 2010; Lillehoj et al ., 2015; Onufrak et al ., 2019). To reduce overconsumption of unhealthy items, policymakers can impose higher tax rates on junk food (Chriqui et al ., 2008; Fletcher et al ., 2010) or strong restrictions on the accessibility of low‐nutrition items sold through vending machines (Kovacs et al ., 2020).…”
Section: Review Findingsmentioning
confidence: 99%
“…(2014) found that in schools where vending machines were available, students consumed unhealthy foods and drinks less frequently. Moreover, some public policy measures (e.g., Arkansas' Act 1220 of 2003, which required restricting access to vending machines, providing healthier items, and promoting physical activity at schools) have been ineffective in reducing obesity among adolescents (Gee, 2018).…”
Section: Review Findingsmentioning
confidence: 99%
“… 91 , 92 A study published in 2018 assessing the effectiveness of this policy concluded that it was very unlikely that the Arkansas Act was having an impact on preventing adolescent overweight and obesity. 93 …”
Section: School-based Interventionsmentioning
confidence: 99%